👤

Bonjour,
A= (2x - 3)(2x+3)-(3x+1)(2x-3)

1 Développe puis réduit A
2 factorise A
3 résoudre l'équation (2x-3)(-x+2)=0​


Répondre :

Coucou

A = (2x - 3) (2x + 3) - (3x + 1) (2x - 3)

= (4x² - 9) - (6x² - 9x + 2x - 3)

= (4x² - 9) - (6x² - 7x - 3)

= 4x² - 9 + 6x² + 7x + 3

= 10x² + 7x - 6

A = (2x - 3) (2x + 3) - (3x + 1) (2x - 3)

= (2x - 3) [ (2x + 3) - (3x + 1) ]

= (2x - 3) (2x + 3 - 3x - 1)

= (2x + 3) (-x + 2)

A = (2x - 3) (-x + 2) = 0

2x - 3 = 0      OU      -x + 2 = 0

2x = 3       OU       -x = -2

x = 3/2       OU       x = 2

Voilà j'espère avoir pu t'aider ^^

Réponse:

a= _3

Explications étape par étape:

(2*_3)=_6/(2*+3)=6/(3*+1)=3/(2*_3)=_6

(_6+6)_(+3+_6)

0__3

_3